2015
DOI: 10.1074/jbc.m114.628701
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Purine Nucleotides Indicates That Purinosomes Increase de Novo Purine Biosynthesis

Abstract: Background: Metabolic enzymes have been hypothesized to assemble into complex to respond to cellular metabolism changes. Results: De novo purine biosynthesis increases in purinosome-containing cells. Conclusion: Purine metabolism is adjusted by purinosome assembly. Significance: This study indicates that purinosome is a functional multienzyme complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 37 publications
6
133
0
1
Order By: Relevance
“…The concept of the metabolon has stirred up more than a little heat, with much expectation but little experimental verification [53]. More recently, experimental evidence for metabolons has appeared [54], including evidence for a glycolytic metabolon in plants [55], and it is becoming clear that metabolons do exist but are dynamic rather than static, being induced when there is a metabolic need, and they almost always assemble on membranes (or on other surfaces such as the cytoskeleton) [56]. In erythrocytes, glycolytic enzymes associate with the anion transporter band 3, in areas where ATP is consumed, forming an ordered complex [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of the metabolon has stirred up more than a little heat, with much expectation but little experimental verification [53]. More recently, experimental evidence for metabolons has appeared [54], including evidence for a glycolytic metabolon in plants [55], and it is becoming clear that metabolons do exist but are dynamic rather than static, being induced when there is a metabolic need, and they almost always assemble on membranes (or on other surfaces such as the cytoskeleton) [56]. In erythrocytes, glycolytic enzymes associate with the anion transporter band 3, in areas where ATP is consumed, forming an ordered complex [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Probing with the remaining four pathway enzymes also showed co-clustering with FGAMS [6]. Immunofluorescence has demonstrated purinosome formation on the endogenous level and provided evidence that the observed compartmentalization is not a consequence of overexpression due to transient transfection [6, 34-36]. Additionally, particle characterization in transient transfected models demonstrated that these enzyme clusters are distinct in size and cell density from processing bodies (P-bodies), stress granules, and aggresomes (Box 2) [37].…”
Section: Discovery Of a Metabolon In Purine Metabolism – The Purinosomementioning
confidence: 99%
“…Purinosome formation and dissociation were found to be modulated by several factors, including the microtubule network and cell signaling through protein phosphorylation (Deng et al, 2012). Significantly, although IMPDH itself appears to be a purinosome component, RR and purinosomes were shown to be distinct cellular bodies, which, under favorable conditions, could be simultaneously visualized within the same cells (Zhao et al, 2015). One cannot dismiss the possibility that RRs form when IMPDH levels required by the cell exceed the amount needed to form purinosome complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Manual counting was performed using the Cell Counter plugin included in Fiji or ImageJ software (Schindelin et al, 2012). With the knowledge that IMPDH localizes to purinosomes as well as RRs (Zhao et al, 2015), only mature filamentous RRs were included in the quantification of the percentage of cells containing RRs. Any foci or short, immature RRs that could not be readily distinguished from purinosomes or other assemblies were not considered RRs.…”
Section: Statistical Analysis and Quantification Of Rrsmentioning
confidence: 99%